Analysis of the central zone of the retina in patients with diabetic macular edema - Mukharram Muhtaramovich Bikbov (Endocrinology Research Centre, 2015)
Aim. To assess morphological changes of retinal layers and optical density of macular pigment in patients with diabetic macular edema (DME) for the diagnostic criterion of pathological process.Materials and methods. 31 patients were divided in two groups. The first group (A) included 19 patients with DME (20 eyes), the second group (B) – 12 patients (20 eyes) without retinal pathology. Both groups were comparable with regard to age. Parameter estimation was conducted with the use of following methods: optical coherence tomography (OCT) of the macular area of the retina; fundus photography with the measurement of macular pigment optical density (MPOD); microperimetry.Results. OCT analysis showed that the inner nuclear and plexiform layers of retina were the most involved in pathological process and revealed significant differences in increase of mean retinal thickness in comparison with the control group. Analysis of MPOD revealed a significant reduction of all parameters in group A compared with the control group. On the basis of microperimetry of the central area of retina in group A light sensitivity indicators were reduced by an average of 9 dB and equaled 9.85 ± 0.09 dB. The analysis showed gross violations of retinal structure and distribution of optical density of macular pigment in patients with DME. Correlation analysis of retinal thickness, functional light sensitivity and optical density of macular pigment traced a strong connection (r = -0.93; p <0.05) between the indices of retinal thickness and MPOD.Conclusions. Diabetic macular edema showed a sharp decrease in optical density of macular pigment determined by deficiency of lutein and zeaxantin. A correlation between quantitative indicator of optical density of macular pigment and area of edema was established. Light sensitivity was significantly reduced in the central part of the retina.